Thin veils strategically interleaved to reduce low velocity damages on CFRP - Amorim, Luís Manuel Machado (2019)
Low velocity impact (LVI) events on carbon fibre reinforced polymers (CFRP) are one of the most problematic issues in composite applications for advanced markets, such as aeronautic, aerospace and army. Due to their own brittleness and layer-by-layer nature, when exposed to LVI solicitations, composites tend to develop internal damages that may be barely visible at naked eye. The high complex field of internal stresses developed in composite laminates during impact usually causes crack initiation and defects between layers, which may propagate (delamination) due to the low toughness that this unreinforced resin rich region exhibits. In this work, to try minimizing this propagation problem, thin veils of different materials (glass, carbon, aramid and polyester), were interleaved between different layers of a carbon/epoxy laminate typically used to produce aircraft components. In addition, to decide between which layers could be better interleave the above referred veils a theoretical study was carried out to evaluate the stresses distribution across laminate thickness when a bending moment is applied, on a carbon/epoxy laminate under study. The new carbon/epoxy laminates using the thin interleaved veils were produced by vacuum bag infusion and their mechanical characteristics and LVI responses compared with those obtained on a non-interleaved one produced in the same processing conditions. Interlaminar shear strength (ILSS) and LVI tests at four different energy impact levels were performed in order to evaluate the respective characteristics of the laminates, their damage tolerance and impact response. All laminates studied were also observed under scanning electron microscopes (SEM) for assessing their processing quality.